Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s12040-013-0378-8
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic seismic hazard assessment of Himachal Pradesh and adjoining regions

Abstract: Seismically active Himachal Pradesh and adjoining regions comprising Himalayan orogenic belt with the experience of the great Kangra earthquake of 1905, has high potential for river valley projects. There are already operating hydropower projects, some under construction and a few more coming up. In view of this it is important to know the ground motion nature for various locales. The present study is about estimation of Peak Ground Acceleration (PGA) for the state of Himachal Pradesh and adjoining regions usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…From the PGA values at class-D for 2475 year return period, the districts of Hamirpur, Bilaspur, Solan, Mandi, Shimla, Kullu, northern parts of Kangra, and the southern parts of Chamba exhibit nearly 35-65% more hazard levels than the districts of Una, Lahaul & Spiti, northern Chamba, eastern Sirmaur, and a small region in the southern part of Kullu. Most importantly, the seismic hazard of the region surrounding Bilaspur, Chamba, and Kullu are found to be the highest within the study region and hazard of this region is higher than the previous studies (NDMA 2011, Patil et al 2014.…”
Section: Seismic Hazard Of Himachal Pradeshcontrasting
confidence: 59%
See 2 more Smart Citations
“…From the PGA values at class-D for 2475 year return period, the districts of Hamirpur, Bilaspur, Solan, Mandi, Shimla, Kullu, northern parts of Kangra, and the southern parts of Chamba exhibit nearly 35-65% more hazard levels than the districts of Una, Lahaul & Spiti, northern Chamba, eastern Sirmaur, and a small region in the southern part of Kullu. Most importantly, the seismic hazard of the region surrounding Bilaspur, Chamba, and Kullu are found to be the highest within the study region and hazard of this region is higher than the previous studies (NDMA 2011, Patil et al 2014.…”
Section: Seismic Hazard Of Himachal Pradeshcontrasting
confidence: 59%
“…Due to the site amplification effects, the values reported in this study are found to be higher in comparison with the values reported by NDMA (2011) for the same return period, whose PGA values presented for class A sites range from 0.05-0.12 g. Similarly, these values are higher than those reported by Parvez et al (2003), obtained by a deterministic approach (design ground acceleration ranges from 0.08-0.15 g). When compared with the case 1 (varying b value) estimates of Patil et al (2014) that range between 0.078-0.15 g, it can be seen that their values underestimates the hazard in this region. When compared with their case 2 (constant b value), the hazard is in the range of 0.12-0.26 g which shows higher estimates for the region except for the Bilaspur and Chamba region.…”
Section: Seismic Hazard Of Himachal Pradeshmentioning
confidence: 94%
See 1 more Smart Citation
“…1a, b below. The tectonic setup of the study area has been studied quite extensively and is easily available (Joshi and Mohan 2010;Patil et al 2014).…”
Section: Study Areamentioning
confidence: 99%
“…It is important to carry out seismic hazard analysis of the region because of its high level of natural seismicity and the presence of segments of major longitudinal tectonic boundary thrusts, namely the Main Central Trust (MCT) and the Main Boundary Thrust (MBT) along with various neotectonic faults traversing through the areas. Several authors have attempted to estimate PSHA for the Indian subcontinent and for different parts of the country (e.g., Khattri et al 1984;Bhatia et al 1999;Mahajan et al 2010;Nath and Thingbaijam 2012;Patil et al 2014). Bhatia et al (1999) estimated expected PGA for the Himalayan region between 0.10 and 0.30 g with 10% probability of exceedance in 50 years.…”
Section: Introductionmentioning
confidence: 99%